Alchemy and Meggy Swann [compact disc, unabridged] - Cushman, Karen (Random House/Listening Library, 2010)
In 1573, the crippled, scorned, and destitute Meggy Swann goes to London, where she meets her father, an impoverished alchemist, and eventually discovers that although her legs are bent and weak, she has many other strengths.